Preparation and Characterisation of complex Bis(pentafluorophenyl) antimony(V) anions of the type [(Rf)2SbCl3X]- - Yadav, Ram Nath Prasad (International Journal of Applied Sciences and Biotechnology, 2013)
A series of hiteherto unreported solid salts of hexa-coordinated anions of the general formula [(Rf)2SbCl3X]- , where Rf = C6F5 ; L = Cl and X = Cl, Br, I, N3, NCS and SeCN have been prepared in the presence of tetraorgano ammonium, phosphonium, arsonium and stibonium counter ions. The complexes have been formulated and characterised on the basis of elemental analysis, molar conductances, molecular weights and solid state IR, solution state 1H NMR and 19F NMR spectral data. The physico-chemical data are consistent with six-coordinate antimony complexes. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8304 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 90-96